036 Ocrelizumab real-world effectiveness in patients with relapsing and primary progressive multiple sclerosis: MuSicalE baseline data. Issue 6 (27th May 2022) - Hobart, Jeremy; Pesch, Vincent van; Rovira, Alex; Alroughani, Raed; Cutter, Gary; Craveiro, Licinio; Dzhenkova, Dima; Kuenzel, Thomas; Kantaria, Rakesh; Trojano, Maria
Abstract : Background: MuSicalE (NCT03593590 ) is an ongoing, observational study assessing ocrelizumab effec- tiveness/safety in patients with relapsing or primary progressive multiple sclerosis (MS) treated with ocre- lizumab in routine care. Methods: Patients with relapsing-remitting MS (RRMS), relapsing secondary progressive MS (rSPMS) or primary progressive MS (PPMS) initiating ocrelizumab per local label/guidelines are included. The primary endpoint is change in SymptoMScreen score (measures 12 common MS symptoms [range, 0–6]; higher scores indicate greater impairment). Results: As of 5 August 2019, 324 patients were eligible for analyses. Overall, patients with rSPMS (n=25) had a longer mean disease duration (16.7 years) versus patients with RRMS (8.6 years; n=243) or PPMS (9.2 years; n=54). Mean [SD] baseline Expanded Disability Status Scale score was higher in patients with rSPMS (5.2 [1.7]) or PPMS (5.0 [1.5]), versus RRMS (3.3 [1.7]). Baseline mean (SD) total SymptoMScreen scores in patients with RRMS, rSPMS and PPMS were 23.0 (13.3), 26.8 (11.9) and 28.7 (11.2), respectively. UK-specific baseline data, including other patient-reported outcomes from secondary end points, will also be presented. Conclusions: Baseline demographics and disease characteristics show expected differences in relapsing and progressive patients. MuSicalE will inform the real-world effectiveness/safety of ocrelizumab in a broad MS population. Recruitment is ongoing. jeremy.hobart@plymouth.ac.uk